Young people's perceptions of the responsibilities of organizations promoting financial capability. (27th January 2014) - Luukkanen, Laura; Uusitalo, Outi
Abstract Today's changing market environment demands financial capability even from young consumers. This article concentrates on the perceptions of young people on the roles and responsibilities of school, public, private and non‐profit sector actors in promoting financial capability among the young. The qualitative data were collected via focus group discussions among young people aged 15–26 in schools and education institutions across Finland. Educational institutions play an important role in the everyday lives of the young but tend to focus on macro‐finance issues in financial education. Banks are seen as professional actors promoting financial capability to the young, but their activities are recognized as profit driven. Public sector and non‐profit organizations are less familiar to young people as providers of financial information but are considered impartial and reliable. It is apparently difficult for young people to differentiate between the activities of the various parties offering financial advice. They would welcome finance‐related information from several actors and from different perspectives. Financial education and financial matters are only interesting to the young when topical. In order to promote a financial capability among young people, the actors involved should become more proactive and cooperate with each other.